Penanaman Toleransi Sejak Dini PAUD Tunas Bangsa National Plus School Purwokerto Timur - ‘Aini , Nur (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga Yogyakarta, 2019)
Learning about tolerance in schools can be delivered with a variety of approaches, strategies,techniques, and media available. Among them with the weaving of religious tolerance valueswhere they are internalized value to students and not only know and do, but also make theknown thing be done it becomes his own unified in and is always used or practiced in everyday life. From the results of the research on the planting of religious tolerance values of early childhood and parents in the PAUD Tunas Bangsa National Plus East Purwokerto School in the know they are planting religious tolerance through (1) habituation activities, (2) Activities and (3) a split religious study. This activity is also interesting, the child is taught to respect the religion around him early on, and will be able to become a life in his social environment both now and future